Potential correlates of burnout among general practitioners and residents in Hungary the significant role of gender, age, dependant care and experience - Ádám Szilvia; Mohos András; Kalabay László; Torzsa Péter (2018)
Burnout is increasingly prevalent among general practitioners (GPs) in Hungary, which may lead to functional impairment and, subsequently, to poor quality of patient care. However, little is known about potential predictors of burnout among GPs. The aim of this study was to explore psychosocial correlates of burnout among GPs and residents in Hungary.We collected socio-demographic and work-related data with self-administered questionnaires in a cross-sectional study among GPs (N = 196) and residents (N = 154). We assessed burnout with the Maslach Burnout Inventory Human Services Survey (MBI-HSS) and calculated the mean level of burnout and the proportion of physicians suffering from low, intermediate and high degree of burnout. To identify potential socio-demographic and work-related correlates of burnout among physicians, we determined Spearman's and Mann-Whitney U correlation coefficients and conducted stepwise linear regression analyses. We deployed Mann-Whitney U test to explore gender disparity in the level of burnout between female and male physicians and between general practitioners and residents.The prevalence of moderate to high level emotional exhaustion, depersonalisation, and impaired personal accomplishment was 34.7, 33.5 and 67.8% as well as 41.0, 43.1, and 71.1% among GPs and residents, respectively. Residents reported significantly lower level of personal accomplishment vs GPs. We identified a significantly higher level of depersonalization among male physicians compared to female physicians. Age correlated negatively with emotional exhaustion and depersonalization and positively with personal accomplishment among GPs. Dependant care was positively associated with burnout among female GPs. Female residents were more likely to report depersonalization. High workload was positively correlated with depersonalization among female GPs. Younger age emerged as the strongest predictor of emotional exhaustion. Male gender and fewer years of experience predicted depersonalization best, and male gender showed a significant predictive relationship with low personal accomplishment.We identified specific socio-demographic and work-related correlates of burnout, which may guide the development of specific and effective organizational decisions to attenuate occupational stress and subsequent burnout as well as functional impairment among GPs, and thus, may improve the quality of patient care.
Keywords: Orvos- és egészségtudomány